Pedagogical education of parents in conditions of destructive influence of values and meanings of mass culture via an informational and educational platform - V. V. Kulishov; O. A. Mosina (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Mass culture has become a part of our lives, its manifestations are expressed in breaking of traditional stereotypes, the uncertainty of the future and the impossibility of determining the trajectory of the future. The current contradictory situation initiated a number of psychological and pedagogical studies aimed at studying its impact on the younger generation and youth. However, the influence of popular culture on students’ parents and the possibility of leveling its influence on the parent community have been poorly studied. The presented problem is being updated in the pedagogical field due to the fact that parents, like their children, are participants in educational relations. Consequently, the problem of developing parental competence in the face of counteracting factors and manifestations of mass culture requires a solution.Goal. The study focuses on theoretical substantiation and experimental verification of the effectiveness of the process of pedagogical education of parents in conditions of destructive influence of values and meanings of mass culture via informational and educational platform.Materials and methods. The theoretical analysis has clarified the concepts of “pedagogical competence” and “accretive potential” of students’ parents. The conceptual foundations of the process of forming parental pedagogical competence in the educational process as a whole, as well as in relation to counteracting actively influencing sociogenic factors, among which is mass culture, were described. The leading research method was a compilation analysis of sociological, philosophical and psychological research aimed at studying the phenomenon of mass culture and its influence on the consciousness of individuals. The results of the implementation of the author's plan in the practice of educational organizations, confirmed by the results of mathematical data processing, were presented in the form of an express review.Results and discussion. The authors present to the reader a theoretical construct intended for the pedagogical education of parents, which is partially reflected in the educational program “Actualization of the creative potential of parents in the context of the destructive influence of the values and meanings of mass culture,” which was tested in a number of educational organizations in the Krasnodar region.Conclusion. The novelty of the research lies in the fact that the problem of pedagogical education of parents of secondary school students is considered in the focus of the influence of the values and meanings of mass culture, in the justification and systematization of the means of the informational and educational platform that can resist its destructive influences.